2009
DOI: 10.1175/2008jtecha1102.1
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Wind Profiler and Polarimetric Weather Radar Method for the Investigation of Precipitation and Vertical Velocities

Abstract: A method is presented by which combined S-band polarimetric weather radar and UHF wind profiler observations of precipitation can be used to extract the properties of liquid phase hydrometeors and the vertical velocity of the air through which they are falling. Doppler spectra, which contain the air motion and/or fall speed of hydrometeors, are estimated using the vertically pointing wind profiler. Complementary to these observations, spectra of rain drop size distribution (DSD) are simulated by several parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
(46 reference statements)
2
17
1
Order By: Relevance
“…It is found that DSDs measured using the distrometer at the surface and estimated using the wind profiler and polarimetric weather radar generally showed good agreement. The DSD retrievals using the wind profiler were improved when the estimates of the vertical wind were included into the analysis, thus supporting the method of Teshiba et al (2009). Furthermore, the the study presents a method of investigating the time and height structure of DSDs.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…It is found that DSDs measured using the distrometer at the surface and estimated using the wind profiler and polarimetric weather radar generally showed good agreement. The DSD retrievals using the wind profiler were improved when the estimates of the vertical wind were included into the analysis, thus supporting the method of Teshiba et al (2009). Furthermore, the the study presents a method of investigating the time and height structure of DSDs.…”
supporting
confidence: 54%
“…Vertical profiles of the polarimetric and DSD data from KOUN are extracted from the RHI or PPI scans and interpolated onto a grid that matches the range gate spacing of the wind profiler (Teshiba et al, 2009). For the data presented in this study, wind profiler and KOUN data from the third range gate above the profiler (600 m a.g.l.)…”
Section: Retrieval Comparisonmentioning
confidence: 99%
See 3 more Smart Citations